APLIKASI PEWARNAAN TITIK PADA GRAPH DALAM PENATAAN BUKU DI PERPUSTAKAAN - Safiil Maarif; Rifa Nurmilah (Jurnal Prinsip Pendidikan Matematika, 2019)
The arrangement of books in a library is one of the activities that must be carried out by a librarian. This is intended to ease library visitors looking for books they need. In this study, researchers provide a new method in organizing those books by applying vertex coloring in graph. This study aims to describe the application of vertex coloring in graph for arranging the books in MTs Al-Hikmah Janti’s library and for identifying the order of books that have been arranged using vertex coloring in graph. This study is a descriptive qualitative study involving documentation method and the object is book arrangement in the library of MTs Al-Hikmah Janti. The main instrument in this study is the researcher himself. Meanwhile, the supporting instruments in this study are the documentation guidelines. The data analysis that researchers employ is making color symbols for each book title, making graphs whose points have been colored according to the agreed color symbols, arranging the books based on the graph that has previously been designed. The way to apply vertex coloring in graph to arrange the books in the library of MTs Al-Hikmah is by making a color symbol to each book title, making a graph starting from rack 1 to rack 4 so that the different color can be assigned to the interconnected points (according to the color symbol which have been made from each lesson). The number of points in the graph is associated to the number of books on each shelf.